Understanding Civil Law in The Context of Contemporary Islam in Indonesia - Karman Karman (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
This article aims to better understand civil law in the context of modern Islam in Indonesia by reviewing several publications that address civil law in the context of Islam from an Islamic standpoint. This article was conducted using a qualitative method. Then, utilizing coding and assessment methods, we examined the data to understand the primary issue fully. Because the research was performed during a pandemic, government restrictions limited public mobility; we relied on secondary data. Finding civil law in an Islamic context, marriage law in an Islamic context that emphasizes an Islamic view following the state's view, how is the evidence for studying civil law in an Islamic context; including the primary law of the individual section, civil family law, and inheritance law in an Islamic context are among the highlights of our findings. We can conclude that Islamic civil law encompasses Munakahat (all aspects of marriage, divorce, and their legal consequences); Wiratsat (all aspects of heirs, heirs, inheritance, and inheritance distribution); and Mu'amalah (all aspects of material things and rights to objects, as well as human relations).